The Influence of Halal Label, Halal Brand Image, Halal Lifestyle, Halal Product Quality, and Halal Awareness on the Purchase Decision of Ms Glow Products - Nabilah, Amaliya; Zulaikha, Siti (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
This study aims to examine and analyze the effect of halal labels, halal brand image, halal lifestyle, halal product quality, and halal awareness on purchasing decisions for MS Glow products. The population in this study are all consumers who buy MS Glow products. This research is included in explanatory research. The sampling technique in this study used a purposive sampling technique. The sample in this study were 192 respondents. The analytical method used in this study is multiple linear regression analysis using SPSS version 25. The results show that halal labels affect purchasing decisions, halal brand image influences purchasing decisions, halal lifestyle influences purchasing decisions, halal product quality influences purchasing decisions purchases, halal awareness affects purchasing decisions. The halal product quality variable has the most dominant influence in determining purchasing decisions for MS Glow products, therefore, companies are required to maintain and improve overall product quality in order to maintain and add consumers amidst very tight competition.